2014
DOI: 10.3748/wjg.v20.i6.1503
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriand gastric cancer: Indian enigma

Abstract: Helicobacter pylori (H. pylori) is a gram negative microaerophilic bacterium which resides in the mucous linings of the stomach. It has been implicated in the causation of various gastric disorders including gastric cancer. The geographical distribution and etiology of gastric cancer differ widely in different geographical regions and H. pylori, despite being labeled as a grade I carcinogen, has not been found to be associated with gastric cancer in many areas. Studies in Asian countries such as Thailand, Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…(17) Approximately 50 percent of the world's population has been estimated to be infected with H. Pylori. (18) The prevalence of H. Pylori infection in India is seen to be around fifty to eighty percent, but the incidence of GC is comparatively low indicating mixed results for the association between H. pylori and GC, (19) Epidemiological studies have shown mixed results for a definite association between H. Pylori and GC in approximately 50% patients, and a negative relationship in the remaining patients. (20) A study in North India on the prevalence of H. Pylori in patients with gastric carcinoma was assessed and correlated with gross appearance and histological types.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Approximately 50 percent of the world's population has been estimated to be infected with H. Pylori. (18) The prevalence of H. Pylori infection in India is seen to be around fifty to eighty percent, but the incidence of GC is comparatively low indicating mixed results for the association between H. pylori and GC, (19) Epidemiological studies have shown mixed results for a definite association between H. Pylori and GC in approximately 50% patients, and a negative relationship in the remaining patients. (20) A study in North India on the prevalence of H. Pylori in patients with gastric carcinoma was assessed and correlated with gross appearance and histological types.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in apoptotic index also correlated with the change in the pattern of Arg/Arg allele in various diseases showing that this allele may prevent the carcinogenic changes by stimulating the Apoptosis in the damaged epithelial cells. This may be the reason of low incidences of Gastric cancer in North India in spite of a relatively higher H. pylori infection thus possibly providing some explaination to Indian Enigma of Gastric Cancer (Pandey, 2010;Misra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The changes caused by this organism at genetic level are not clear and therefore the present study was aimed to provide experimental evidence of relationship between H. pylori infection and gastric carcinogenesis by elucidating its relationship with p53 polymorphism at codon 72 and change in the rate of Apoptosis to elucidate the reasons for decreased prevalence of gastric cancer with H. pylori despite high rate of infection Ther aim of this study was to find the possible explanation of Indian enigma of gastric cancer (Singh and Ghosha, 2006;Pandey et al, 2010;Misra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of PU varies geographically and within individual countries. This was shown in India , the differences being attributed possibly to variation in H. pylori strains, host genetic makeup, environmental factors, and different infection rates in the population. A Brazilian study compared endoscopy records between 1997–2000 and 2007–2010.…”
Section: Peptic Ulcer Diseasementioning
confidence: 91%